Dampak dari Pelanggaran Etika Bisnis terhadap Hak Pekerja di PT Alpen Food Industry (AICE) - Meylia Adillah; Vidiyana Anggrayni; Azra Nabila; Mohamad Zein Saleh (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the impact of violations of business ethics on workers' rights at PT Alpen Food Industry, known as a leading ice cream producer in Southeast Asia. The company faces a number of violations, including inadequate working conditions, inadequate wage payments, excessive working hours, and discrimination against female workers. The study uses a qualitative method with a literature review approach, where data is obtained from various articles, reports, and relevant documents. The results of the study indicate that violations of workers' rights, such as violations of leave rights, unsafe working conditions, gender discrimination, and non-compliance with labor laws, have a significant impact on workers' welfare, the company's reputation, and its business sustainability. The novelty of this study lies in the in-depth analysis of the implications of violations of business ethics on the sustainability of companies in the food industry sector, with the implication that internal policy reform, strengthening law enforcement, and consistent application of business ethics are needed to create a safe, fair, and conducive work environment.